Clinical outcomes of subcutaneous vs. transvenous implantable defibrillator therapy in a polymorbid patient cohort - Kattih, Badder; Operhalski, Felix; Boeckling, Felicitas; Hecker, Florian; Michael, Felix; Vamos, Mate; Hohnloser, Stefan H.; Erath, Julia W. (Frontiers in Cardiovascular Medicine, 2022)
Background: The subcutaneous implantable cardioverter-defibrillator (S-ICD) has been designed to overcome lead-related complications and device endocarditis. Lacking the ability for pacing or resynchronization therapy its usage is limited to selected patients at risk for sudden cardiac death (SCD). Objective: The aim of this single-center study was to assess clinical outcomes of S-ICD and single-chamber transvenous (TV)-ICD in an all-comers population. Methods: The study cohort comprised a total of 119 ICD patients who underwent either S-ICD (n = 35) or TV-ICD (n = 84) implantation at the University Hospital Frankfurt from 2009 - 2017. By applying an inverse probability-weighting (IPW) analysis based on the propensity score including the Charlson Comorbidity Index (CCI) to adjust for potential extracardiac comorbidities, we aimed for head-to-head comparison on the study composite endpoint: overall survival, hospitalization, and device-associated events (including appropriate and inappropriate shocks or system-related complications) Results: The median age of the study population was 66.0 years, 22.7 % of the patients were female. The underlying heart disease was ischemic cardiomyopathy (61.4 %) with a median LVEF of 30 %. Only 52.9 % had received an ICD for primary prevention, most of the patients (67.3 %) had advanced heart failure (NYHA class II - III) and 16.8 % were in atrial fibrillation. CCI was 5 points in TV-ICD patients versus 4 points for patients with S-ICD (p = 0.209) indicating increased morbidity. The composite endpoint occurred in 38 patients (31.9 %), revealing no significant difference between patients implanted with an S-ICD or TV-ICD (unweighted HR 1.50, 95 % confidence interval (CI) 0.78 to 2.90; p = 0.229, weighted HR 0.94, 95% CI, 0.61 - 1.50, p = 0.777). Furthermore, we observed no difference in any single clinical endpoint or device-associated outcome, neither in the unweighted cohort nor following inverse probability-weighting. Conclusion: Clinical outcomes of the S-ICD and TV-ICD revealed no differences in the composite endpoint including survival, freedom of hospitalization and device-associated events, even after careful adjustment for potential confounders. Moreover, the CCI was evaluated in a S-ICD cohort demonstrating higher survival rates than predicted by the CCI in young, polymorbid (S-)ICD patients.